2012
DOI: 10.5935/1984-6835.20120012
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Aspects of the Essential Oil of Indian Cloves

Abstract: Abstract:The Indian clove (Syzygium aromaticum, Myrtaceae) is a well appreciated spice since the ancient times not only by its flavor and culinary qualities, but also because of its therapeutic uses. Several popular and traditional applications have been reported in literature as well as numerous scientific studies on its activities. In this work we present a synopsis and discussion on S. aromaticum to provide the readers some useful information on the historical aspects, the chemical composition and its large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
1
17
0
3
Order By: Relevance
“…In the present study, 5 g kg -1 dose were used with similar results. Finally, the clove plant is well studied and has product patents for several uses, with the main substance studied eugenol, probably the active ingredient that causes repellency and insect mortality (Affonso et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, 5 g kg -1 dose were used with similar results. Finally, the clove plant is well studied and has product patents for several uses, with the main substance studied eugenol, probably the active ingredient that causes repellency and insect mortality (Affonso et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…14 Despite not having its mechanism of action well elucidated yet, N,N-diethyl-3-methylbenzamide (DEET) is the main repellent in use today against A. gambiae. 2,3,4,6,15 Tsitsanou et al 14 suggested that this molecule targets AgOBP 1 , blocking the binding site of the attractive molecules, and published the 3D structure of the AgOBP 1 -DEET complex as the first example of a repellent recognized by an OBP. This achievement should give a significant impulse to the drug design of new repellents as it provides the first known target.…”
Section: Introductionmentioning
confidence: 99%
“…Next, these molecules are transported to the olfactory receptor neurons (ORN), located in the dendritic membranes at the antenna sensory bristles, driving the mosquito's attention to the potential meal. 3,9,[11][12][13][14] Studies by Biessmann et al 11 have proved the importance of OBP for smell recognition in the search for food, in mating and other activities. 3,12,14 Among the 60 types of OBP coded in the A. gambiae genoma, the Anopheles gambiae odorant binding protein (AgOBP 1 ) was found in higher levels in the antennas of females when compared to males and its levels were observed to reduce when the females feed on blood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations